Women of the Catacombs : Memoirs of the Underground Orthodox Church in Stalin's Russia - Vasilevskai︠a︡, V. I︠A︡. (Vera I︠A︡kovlevna); Robson, Roy R.; Daniel, Wallace L.; Daniel, Wallace L. (Book collections on Project MUSE., 2021)
"This book offers an intimate portrait of two courageous young Russian women and their struggles to maintain their integrity and personal values in Stalin's Russia, from the 1930s to the 1950s" --